2008
DOI: 10.1093/jac/dkn496
|View full text |Cite
|
Sign up to set email alerts
|

Pharmacokinetics of ceftiofur hydrochloride in pigs infected with porcine reproductive and respiratory syndrome virus

Abstract: The pharmacokinetic profile of ceftiofur is altered in PRRSV-infected pigs due to the decreased plasma ceftiofur concentration compared with clinically healthy pigs.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
31
0

Year Published

2010
2010
2020
2020

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(31 citation statements)
references
References 13 publications
0
31
0
Order By: Relevance
“…This timing targeted the peak viremia of the wild-type virus, VR-2385, based on previous literature (Johnson et al, 2004). Tantituvanont et al (2009) found similar results with PRRSv challenged pigs and the pharmacokinetics of a shorter acting ceftiofur preparation, ceftiofur hydrochloride. Similar to observations in the present study with CCFA, ceftiofur hydrochloride in PRRSv challenged pigs was reported to have higher Cl/F, higher Vz/F, and lower AUC.…”
Section: Discussionmentioning
confidence: 78%
See 1 more Smart Citation
“…This timing targeted the peak viremia of the wild-type virus, VR-2385, based on previous literature (Johnson et al, 2004). Tantituvanont et al (2009) found similar results with PRRSv challenged pigs and the pharmacokinetics of a shorter acting ceftiofur preparation, ceftiofur hydrochloride. Similar to observations in the present study with CCFA, ceftiofur hydrochloride in PRRSv challenged pigs was reported to have higher Cl/F, higher Vz/F, and lower AUC.…”
Section: Discussionmentioning
confidence: 78%
“…There is a reason to believe that a PRRSv infection could impact absorption, volume of distribution, and clearance. Suggested mechanisms by which a general disease state may alter PK include changes in capillary permeability, hepatic function, renal function, plasma proteins, and vascular pH (Mengelers et al, 1995;Agerso et al, 2000;Post et al, 2002;Riviere, 2009;Tantituvanont et al, 2009).…”
Section: Discussionmentioning
confidence: 99%
“…Other studies have also shown significantly higher AUC of docetaxel and reduced glomerular filtration rate, suggesting changes in renal CYP in rats injected with the recombinant adenovirus expressing -galactosidase (Le et al, 2006;Wonganan et al, 2009). On the contrary, significantly reduced C max and AUC of ceftiofur hydrochloride were observed in pigs infected with porcine reproductive and respiratory syndrome virus compared to the uninfected pigs (Tantituvanont et al, 2009). …”
Section: Pk/pd Studiesmentioning
confidence: 95%
“…Ceftiofur is the only injectable antimicrobial approved as a daily dosage of 1.1-2.2 mg/kg body weight, by Food and Drug Administration (FDA) in goats for the treatment of respiratory diseases associated with P. multocida and M. haemolytica. Pharmacokinetic properties of ceftiofur have been investigated in cattle (Soback et al, 1991;Erskine et al, 1995;Brown et al, 1996Brown et al, , 2000Okker et al, 2002;von Krueger et al, 2013;Gorden et al, 2016), camel (Goudah, 2007), goat (Courtin et al, 1997;Dore et al, 2011), horse (Collard et al, 2011;Credille et al, 2012;Fultz et al, 2013;Macpherson et al, 2013), sheep Rivera-Garcia et al, 2014), pig (Brown et al, 1999;Tantituvanont et al, 2009;Day et al, 2015) and alpacas (Dechant et al, 2013). Recently, a long-acting formulation of ceftiofur, ceftiofur crystalline-free acid (CCFA) (CCFA-SS; EXCEDE http:// pfizerah.com), has been approved in the United States for the treatment of bovine respiratory disease and foot rot when administered as a single dose of 6.6 mg/kg of body weight.…”
Section: Introductionmentioning
confidence: 99%